Pendampingan Edu-Wisata Seni Budaya Jawa di Yayasan Kampung Seni Kentingan Surakarta dalam Mendukung Kota Solo sebagai Kota Wisata Budaya Internasional - Kundharu Saddhono; Muhammad Rohmadi; Ani Rakhmawati; Raheni Suhita; Budhi Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program was carried out with the aim of developing the concept of Javanese cultural art edu-tourism at the Kentingan Art Village Foundation in Surakarta as an academic contribution to realizing the vision of Solo City as an internationally recognized cultural tourism destination. The approach adopted was participatory and collaborative, involving various stakeholders such as foundation managers, local artists, academics, and the surrounding community. Through this program, the service team sought to strengthen managerial skills in art-based tourism management, enrich educational content that highlights Javanese cultural values, and develop digital promotion strategies to expand the reach of visitors. The results of the mentoring activities indicated a significant improvement in the capacity for managing art events and organizing the tourism area at Kentingan Art Village. The edu-tourism package developed successfully integrated elements of education, entertainment, and cultural preservation in a harmonious manner. In addition, the program encouraged growing interest from educational institutions and creative communities seeking to make Kentingan Art Village a site for cultural learning. Overall, this community service initiative made a tangible contribution to strengthening the community-based cultural tourism ecosystem in Solo City and serves as a model for developing sustainable tourism destinations rooted in Javanese local wisdom.